2021
DOI: 10.3389/fpsyg.2020.620027
|View full text |Cite
|
Sign up to set email alerts
|

Remote W.A.R.A. Compared With Face-to-Face W.A.R.A.: A Pilot Study

Abstract: BackgroundSince the outbreak of the COVID-19 pandemic and its social restriction measures, online therapy is a life-saving possibility for patients with acute stress. Wiring Affect with ReAttach (W.A.R.A.) is a brief psychological intervention aiming to decrease negative affect, that can be offered online.MethodsWe assessed the effect of remote W.A.R.A. on negative affect in 37 patients. Consequently, we compared the effect of remote W.A.R.A. versus face-to-face W.A.R.A on negative affect in a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…On the contrary, in Weerkamp‐Bartholomeus et al. study (Weerkamp‐Bartholomeus et al., 2020 ), although the remote therapy significantly reduced the negative affect but they showed the preference of face to face therapy. This result is in line with findings of a RCT of 325 Chicago‐area primary care patients with major depressive disorder who received Telephone‐administered Cognitive Behavioral Therapy (T‐CBT) versus face to face Cognitive Behavioral Therapy (CBT) and it was revealed that although Patients showed significant improvement in depression across both treatments but those receiving face‐to‐face CBT were less depressed than those receiving T‐CBT (Mohr et al., 2012 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On the contrary, in Weerkamp‐Bartholomeus et al. study (Weerkamp‐Bartholomeus et al., 2020 ), although the remote therapy significantly reduced the negative affect but they showed the preference of face to face therapy. This result is in line with findings of a RCT of 325 Chicago‐area primary care patients with major depressive disorder who received Telephone‐administered Cognitive Behavioral Therapy (T‐CBT) versus face to face Cognitive Behavioral Therapy (CBT) and it was revealed that although Patients showed significant improvement in depression across both treatments but those receiving face‐to‐face CBT were less depressed than those receiving T‐CBT (Mohr et al., 2012 ).…”
Section: Discussionmentioning
confidence: 87%
“…Participants were individuals prone to mental illnesses like depression and GAD due to the COVID‐19 pandemic and its consequences on lifestyle. Interventions in these studies consisted of a wide range of telecommunication methods, including telephone contacts (Alessi et al., 2021 , 2022 ; Kahlon et al., 2021 ; Lai, Yan, et al., 2020 ), messaging platforms (Aguilera et al., 2021 ), online methods, for example, videoconference, and online apps (Al‐Alawi et al., 2021 ; Fiol‐DeRoque et al., 2021 ; Lai, Yan, et al., 2020 ; Sanchez‐Guarnido et al., 2021 ; Shapira et al., 2021 ; Summers et al., 2021 ; Watts et al., 2020 ; Weerkamp‐Bartholomeus et al., 2020 ). The outcome assessment was different between the articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crisis situations, however, may also stimulate creativity, resulting in innovative initiatives. During this pandemic, the already ongoing digitalization of our society has overcome its last persistent hurdles, with results that have indeed been promising 3 . This offers opportunities for implementation of mHealth interventions that are transdiagnostic and empowering, probably particularly suitable for the next generation of help‐seeking (emerging) adults 4 , as they completely grew up in a digitalized world.…”
mentioning
confidence: 99%